Peningkatan Hasil Belajar Peserta Didik menggunakan Model Problem Based Learning pada Materi Data di Kelas V SDN 24 Ujung Gurun - Agustina, Sovia; Masniladevi, Masniladevi (TSAQOFAH, 2025)
The low learning outcomes of Grade V students at SDN 24 Ujung Gurun are attributed to a lack of self-confidence and active participation in a teacher-centered learning process. This study aims to describe the improvement of student learning outcomes through the implementation of the Problem Based Learning (PBL) model on data-related material. The research employed Classroom Action Research (CAR) using both quantitative and qualitative approaches, conducted in two cycles through the stages of planning, implementation, observation, and reflection. The research subjects included the classroom teacher, the researcher as practitioner, and 27 Grade V students. Data collection techniques comprised observation, tests, and non-test instruments. The results showed improvement across several aspects: the quality of teaching modules increased from 87.49% to 95.83%; teacher performance improved from 88.38% to 96.42%; student engagement rose from 88.38% to 94.5%; and the average learning outcome score increased from 70.32 (Fair category) to 89.02 (Good category). These findings demonstrate that the Problem Based Learning model is effective in enhancing student learning outcomes in data-related topics at the elementary level.